PERENCANAAN STRUKTUR GEDUNG HOTEL PERSONA JAKARTA - Adhitiyo Eka Mahaendra; Prasetya Dita Perdana; Himawan Indarto; Bambang Pardoyo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Persona Hotel located on the main route from Bekasi to Jakarta, in area Jatiwaringin 60. Hotel Persona will be built vertically with the number five floors consisting of four floors and a roof floor.Building structure designed use Special Moment Resisting Frame System based on Concrete requirements for structural building Codes (SNI 2847-2013) Analysis of seismic loading was conducted using equivalent static method based on Indonesian Earthquake Resistant Building Codes (SNI 03-1726-2012). In designing this building structure, we used the concept of capacity design. The purpose of this concept was to provide enough ductility by designing plastic hinges on beam. In order to guarantee plastic hinges are formed on the beams, the columns should be designed to be stronger than the beams (Strong Column Weak Beam). The foundation was designed as bored pile, because the soil in that area was hard soil type. The results of the structural analysis show that the Hotel Building structure was able to withstand the designed earthquake loading.